GENETIC DIVERSITY OF WINTER BREAD WHEAT (Triticum aestivum L. ssp. vulgare) - Sonja Petrović (Poljoprivreda, 2011)
Diversity was analyzed based on agronomic and morphologic traits and molecular data. The main objectives of this study were: 1. to estimate genetic diversity of wheat germplasm using agronomic and morphologic traits and molecular markers, 2. to investigate the existence of genetic erosion within tested wheat germplasm, 3. to explore potential utilization of combination of agronomic, morphologic and molecular markers in plant breeding. Forty winter bread wheat varieties were used originating from Croatia, Austria, France, Italy and Russia. Field trial was conducted during two vegetation years (2007/2008, 2008/2009) in three replications according to randomized block design. Ten traits were included in agronomic and morphologic analysis. Composition of high molecular weight glutenin subunits (HMW GS) was evaluated for 16 varieties, whereas literature data are used for the rest. Starch composition analysis was based on amylose and amylopectin isolation, their quantity and ratio. For the SSR analysis 26 microsatellite primers were used, and for the AFLP analysis four primer combinations. Statistical analysis was performed using SAS Software 9.1.3, NTSYS ver.2.2., Arlequin ver2.0. and Powermarker ver.3.25. Analyzed varieties displayed highly significant differences (p<0,001) for all agronomic traits and for amylose/amylopectin ratio. High variability of HMW GS was found among varieties. Estimation of genetic diversity based on morphologic and molecular data were used to construct dendograms. AMOVA was used to evaluate variability based on molecular data. Genetic diversity was estimated among and within morphologic and molecular data. SSR and AFLP markers showed efficient discrimination power between highly related genotypes. Significant correlation was found out between two molecular methods which showed more accurate estimate of genetic diversity than by agronomic and morphologic data.